AL-QUR'ANIC INSIGHTS ON GENDER AND IMPLICATIONS FOR ISLAMIC LAW - Samsidar Jamaluddin; Hasyim Haddade; Andi Moh. Rezki Darma; Mulyanti (Jurnal Al Tasyri'iyyah, 2024)
ABSTRACT This study aims to describe the Qur'anic insights on gender and implications for Islamic law. This research is qualitative research, the type of research is library research. The data collection method used is literature study. The results showed that the Qur'anic insights about gender and implications for Islamic law are the transformation of Islamic legal thought related to the issue of equal relations between men and women in the text of the Qur'an and hadith, the transformation of thought in the field of professions such as female judges and other professions that are generally carried out by men, becoming a source of inspiration for the emergence of legislation that favors the interests of women. Keywords: Qur'anic Insights; Gender; Implications; Islamic Law.